siRNA-mediated knockdown of FoxP3 promotes the ratio of T-helper 1 (Th1) to Th2 in chronic hepatitis B patients - Li XIAOLIANG,; Yu YONGSHENG,; Tang ZHENGHAO,; Zang GUOQING, (Turkish Journal of Gastroenterology, 2019)
-